Leukocytoclastic Vasculitis in a Patient With Crohn Disease: A Case Report - Mark Daniele Bugada BS; Vamsi K. Emani MD (SAGE Publishing, 2023)
Leukocytoclastic vasculitis (LCV) is an idiopathic small vessel vasculitis. Leukocytoclastic vasculitis can be found in a spectrum of diseases and is noted as a rare extraintestinal manifestation of Crohn disease. This case report examines a 55-year-old man with a previous diagnosis of Crohn disease who was admitted after 5 days with a persistent rash. A biopsy confirmed LCV, and the patient followed up with dermatology for outpatient treatment. This study adds to the sparse medical literature on LCV cases relating to Crohn disease.